2013
DOI: 10.1186/1756-3305-6-129
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Culex pipiens/restuans population dynamics by interval lagged weather data

Abstract: BackgroundCulex pipiens/restuans mosquitoes are important vectors for a variety of arthropod borne viral infections. In this study, the associations between 20 years of mosquito capture data and the time lagged environmental quantities daytime length, temperature, precipitation, relative humidity and wind speed were used to generate a predictive model for the population dynamics of this vector species.MethodsMosquito population in the study area was represented by averaged time series of mosquitos counts captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 31 publications
1
70
1
Order By: Relevance
“…(Carrieri et al ), and in this area of study we observed an inversely proportional relationship with temperature. The importance of precipitation is indicated by many authors (Becker et al , Lebl et al ), noting that more days of rainfall at the beginning and end of the year will lead to increased formation and persistence of larval mosquito habitats and mosquito populations remaining steady during the year (Rosà et al ). This factor may adversely affect the development of mosquitoes according to the intensity of precipitation and type of larval habitat (Carrieri et al ).…”
Section: Discussionmentioning
confidence: 99%
“…(Carrieri et al ), and in this area of study we observed an inversely proportional relationship with temperature. The importance of precipitation is indicated by many authors (Becker et al , Lebl et al ), noting that more days of rainfall at the beginning and end of the year will lead to increased formation and persistence of larval mosquito habitats and mosquito populations remaining steady during the year (Rosà et al ). This factor may adversely affect the development of mosquitoes according to the intensity of precipitation and type of larval habitat (Carrieri et al ).…”
Section: Discussionmentioning
confidence: 99%
“…), while the mean lifespan of adult Culex under summer field conditions in the absence of predation risk is only ~7 d (Lebl et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Block ANOVA was used to compare the mosquito population densities of urban and rural areas. We applied the same data transformation used in previous approaches (Lebl et al 2013), and mosquito counts were standardized to females per trap per month, and these standardized counts were transformed by log(yϩ1) to normalize the data and control the variance. We adopted the SpearmanÕs rank correlation, which is insensitive to transformation using monotonic functions.…”
Section: Methodsmentioning
confidence: 99%